2021
DOI: 10.1038/s41598-021-94892-0
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-based secondary preventive follow-up by telephone reduced recurrence of cardiovascular events: a randomised controlled trial

Abstract: Enhanced follow-up is needed to improve the results of secondary preventive care in patients with established cardiovascular disease. We examined the effect of long-term, nurse-based, secondary preventive follow-up by telephone on the recurrence of cardiovascular events. Open, randomised, controlled trial with two parallel groups. Between 1 January 2010 and 31 December 2014, consecutive patients (n = 1890) admitted to hospital due to stroke, transient ischaemic attack (TIA), or acute coronary syndrome (ACS) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…More than half of the patients in this IS and TIA population were included in a RCT that investigated whether a nurse-led and telephone-based follow-up strategy could decrease MACE in a population after IS, TIA, or acute coronary syndrome. It showed that the intervention improved not only blood pressure and lipid levels 37 , but also decreased recurrence of MACE, suggesting that a structured long-term follow-up of modifiable risk factors could lead to fewer MACE 38 .…”
Section: Discussionmentioning
confidence: 98%
“…More than half of the patients in this IS and TIA population were included in a RCT that investigated whether a nurse-led and telephone-based follow-up strategy could decrease MACE in a population after IS, TIA, or acute coronary syndrome. It showed that the intervention improved not only blood pressure and lipid levels 37 , but also decreased recurrence of MACE, suggesting that a structured long-term follow-up of modifiable risk factors could lead to fewer MACE 38 .…”
Section: Discussionmentioning
confidence: 98%
“…The importance of antiplatelet and lipid-lowering therapy has been widely discussed, together with the importance of maintaining a healthy lifestyle is also essential ( 30 ). Excluding the integrated care approach, regular follow-up of TIA patients could reduce the recurrence of cardiovascular events ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Telephone follow-up is a widely used follow-up method [ 12 ] that enables discharged patients to receive health guidance and medical services related to their disease at home and reduces the recurrence of cardiovascular events during long-term follow-up. [ 1 ] It is well known that Chinese doctors are often overwhelmed by overwork and do not have the time and energy to carefully instruct each patient on medication use. Clinical pharmacists can compensate for this deficiency, which can not only reduce the burden on doctors but also solve the problems of patients in the follow-up process and meet the needs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Peptic ulcer is a chronic disease; its development and prognosis are closely associated with patient awareness of the disease and treatment compliance, and family treatment after discharge is associated with the treatment effect. A study by Thomas Mooe et al [ 1 ] showed that nurse-based secondary preventive follow-up by telephone reduced the recurrence of cardiovascular events. Several studies on hypertension, diabetes, heart failure, rheumatoid arthritis, and cancer have also demonstrated the benefit of telephone follow-ups in these patients.…”
Section: Introductionmentioning
confidence: 99%